Durum wheat yield sustainability or ecosystem sustainability?: Effects of state policies on farmers' behaviour in Algeria - Malki M.; Redjel N. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Durum wheat is a basic staple food in Algeria. Since the independence, state agricultural policies, aiming at improving the level of durum wheat output, introduced distorting incentives and caused a farmer negative behaviour towards natural resources. Being conceived and implemented upon a standardised manner, these policies yielded a dramatic degradation of the ecosystem. This paper aims to introduce two examples of ecosystems: the one concerns the potential agro-ecological zones of northern Algeria, the other concerns the marginal lands in steppic and sub-steppic areas. In both ecosystems, durum wheat is cultivated either as a long tradition or as a consequence of standardised state policies. The paper's conceptual framework on sustainability focuses on the concept of the 'critical triangle of sustainability' or 'the 3E's of sustainability' (that are Efficiency or economic growth, Equity or poverty alleviation, and Ecology or environment conservation).
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)